Emotional intelligence and clinical performance/retention of nursing students - Chelsea Marvos; Frankie B Hale (Elsevier, 2015)
Objective: This exploratory, quantitative, descriptive study was undertaken to explore the relationship between clinical performance and anticipated retention in nursing students. Methods: After approval by the university's Human Subjects Committee, a sample of 104 nursing students were recruited for this study, which involved testing with a valid and reliable emotional intelligence (EI) instrument and a self-report survey of clinical competencies. Results: Statistical analysis revealed that although the group average for total EI score and the 6 score subsets were in the average range, approximately 30% of the individual total EI scores and 30% of two branch scores, identifying emotions correctly and understanding emotions, fell in the less than average range. This data, as well as the analysis of correlation with clinical self-report scores, suggest recommendations applicable to educators of clinical nursing students. Conclusions: Registered nurses make-up the largest segment of the ever-growing healthcare workforce. Yet, retention of new graduates has historically been a challenge for the profession. Given the projected employment growth in nursing, it is important to identify factors which correlate with high levels of performance and job retention among nurses. There is preliminary evidence that EI "a nontraditional intelligence measure" relates positively not only with retention of clinical staff nurses, but with overall clinical performance as well.